(3QSGdI aj Gdadcs - (3eLghds
(3ChdgG (B:s
(3HSe Gddg (B... (3hGdKGfj efg (B.. (3heOI bWYgG EjGg ReGf GdUja ajg hGdKGdK efg GdGYJOGd (B..(3bWYgG EjGg ReGf GdNQja hGdQGHY (B..s
(3BNQgG (B:s
... (3CjGe GdSfI GdbeQjI GdGUWdGMjI KdGKeGFI hCQHYI hNeSjf jheG hNeSjf jhe hSOSg hgPg GdSfI fGbUI Yf GdSfI GdTeSjI GdMbjbjI HYTQI CjGe hYTQjf SGYI hfUa SGYI HGdJbQjH (B, (3JeJs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs